Network and internetwork security : - Stallings, William (Prentice Hall, 1995)
Comprehensive in approach, this introduction to network and internetwork security provides a tutorial survey of network security technology, discusses the standards that are being developed for security in an internetworking environment, and explores the practical issues involved in developing security applications.